Revisiting R.K. Narayan’s the guide on silver screen - Pushp Lata; Sanjay Kumar; Akasy Dey; Oindrilla Chakraborty (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
It is evident that an adaptation can be original or unoriginal but its presence is inarguable. Therefore this study does not make an attempt to see why a novel is adapted for cinematic projection, but tries to assess how effectively the adaptation is done. It is clear that the investigation is biased by both the eye and the eyepiece. R.K. Narayan adopts the individual as his reference and looks inward, affecting a microcosmic view of society and its problems. He showcases the idiosyncrasies of the characters and superimposes them on one another to come up with a layered structure of societal inconsistency and prejudice. On the other hand, Vijay Anand is inclined towards a top-down approach, treating issues and personalities first and then individuals and specific problems. For this purpose, this paper focuses on a famous work, ‘Guide’, by R. K. Narayan) and its adaptation for the movie Guide. It also examines how the film is different from its original source and how far a novel is adapted for cinematic projection, but tries to assess how the changes in the adaptation connote different insinuations and subtleties. It also explores how far the changes are independent of its original source and discusses the impact of these cinematic changes.